GIS-based morphometric analysis of the Dewana basin, Sulaimani, Kurdistan, Iraq - Ahmed, Lanja H.; Al-Qayim, Basim (Sulaimani Journal for Pure and Applied Sciences, 2016)
An integrated remote sensing data are used in a detailed morphometric study of the Dewana drainage basin, Sulaimani Governorate of the northeastern part of Iraq. The basin is considered as a good example of a medium scale drainage basin of a mountainous terrain with variable geomorphological processes and landscapes. Major basin divides recognized by the homoclinal ridges of Baranan Mountain to the northeast and Sagerma Mountain to the southwest. Satellite images as well as Digital Elevation Model with topographic, geologic, and structural maps were used in addition to field investigations to perform a GIS-based drainage network and morphometric analysis. An analysis which becomes important sources of the area with increasing agricultural development. Arc GIS 9.3 was used for digitizing, measuring and drawing the spatial data of these analyses. Detailed morphometric analysis was applied to the Dewana basin, using variable geomorphological and hydrogeomorphological parameters, by calculating network aspects from two sets of topographic maps at scale of 1:20,000 and 1:50,000. Different sets of morphometric parameters were calculated such as: linear, relief and aerial parameters. Morphometric analysis results are discussed and correlated with each other and to standard values to evaluate fluvial-geomorphic evolution of the basin. The study shows that the Dewana basin is of the 6th order drainage basin, with relatively, high values of drainage density and basin relief which implies that surface runoff is not rapidly removed from the basin, making it susceptible to gully erosion and landslides. Shape parameters of the basin indicate that it has elongated form, which reflects strong structural controls on the morphology of the basin. Drainage pattern is dominated by dendritic, sub-parallel to sub-trellis types which emphasize structural controls in addition to variable lithologic characters of the basin rocks.
Keywords: Morphometic Analysis,GIS; Kurdistan; Iraq